ANALISIS PENGARUH ANGKA HARAPAN HIDUP, ANGKA MELEK HURUF, TINGKAT PENGANGGURAN TERBUKA DAN PENDAPATAN DOMESTIK REGIONAL BRUTO PERKAPITA TERHADAP KEMISKINAN PADA KABUPATEN/ KOTA DI PROVINSI SULAWESI TENGAH TAHUN 2010-2013 - Anggadini, Fima (Katalogis, 2015)
This research was conducted in several districts/city in Central Sulawesi Province in order to determine the effect of life expectancy, literacy rate, opened unemployment rate, and gross domestic regional income per capita on poverty at the districts/city in the province of Central Sulawesi. The analysis used in this study is Panel Data Regression. The results show: first, life expectancy and gross regional domestic regional income have a negative and significant impact on the poverty level in the districts/city in the Province of Central Sulawesi. Second, the opened unemployment rate has a positive and significant effect on the poverty level in the districts/city in the province of Central Sulawesi. Third, literacy rates show a positive effect and insignificant effect on the poverty level in the districts/city in the Province of Central Sulawesi. Fourth, simultaneously affect the poverty in the districts/city in the Province of Central Sulawesi.